Daring to Be Bad : Radical Feminism in America 1967-1975, Thirtieth Anniversary Edition - Echols, Alice (Book collections on Project MUSE., 2019)
"Combines intellectual and social history with collective biography to present the first historical study of the radical feminist movement in America."--Publisher's description